Perbedaan Kepuasan Kerja Perawat Antara RSU GMIM Pancaran Kasih dengan RS Wolter Mongisidi Manado - Ribka Anggie Maria Abuno; Diana Vanda Daturara Doda; Jeini Ester Nelwan (Lembaga Pengembangan Kinerja Dosen, 2025)
Jobstreet reported that job satisfaction in Indonesia in 2022 based on a survey of 17,623 respondents, showed that 73.0% of employees were dissatisfied with their jobs (Soejanto, dkk, 2025). Based on international research on 43,000 nurses from 700 hospitals in the United States, Canada, England, Scotland, and Germany, it showed that the number of nurses' dissatisfaction with their jobs was around 17% in Germany to 41% in America (Rusmianingsih, 2024). Nurse job satisfaction is one of the factors that affects nurse work productivity, because when nurses feel dissatisfied with their work and the services produced are less than optimal (Mulyaningtyas, et al. 2021). The purpose of this study was to determine the difference in nurse job satisfaction between RSU GMIM Pancaran Kasih and RS Wolter Mongisidi Manado. The type and design of the research used is descriptive analytical survey with cross-sectional research design (cross-sectional study). The number of samples taken was 100 respondents based on purposive sampling technique. The research instrument to measure the level of job satisfaction used the Job Satisfaction Scale (JSS) questionnaire. The results showed that the majority of nurses at Wolter Mongisidi Hospital Manado felt very satisfied 37 (74.0%) and there were no nurses who felt very dissatisfied while at GMIM Pancaran Kasih Hospital the majority of nurses felt very satisfied 23 (46.0%) and there were no nurses who felt very dissatisfied. The data were analyzed using the Mann-Whitney test which obtained a p value of 0.001. These results indicate that p <a which means there is a difference in the level of job satisfaction of nurses at GMIM Pancaran Kasih Hospital and Wolter Mongisidi Hospital Manado. The conclusion of this study is that there is a difference in the level of job satisfaction of nurses at GMIM Pancaran Kasih Hospital and Wolter Mongisidi Hospital. This study shows that the six dimensions of job satisfaction, namely the work itself, salary, promotion, supervision, coworkers, and work environment, all have different dimensions between nurses at GMIM Pancaran Kasih Hospital and Wolter Mongisidi Hospital.